The Use of Fractional Cards for Fraction Learning in The Fifth Grade Students of Elementary School - Indriani, Ari ((JRAMathEdu) Journal of Research and Advances in Mathematics Education, 2016)
This research aims to investigate the use of fractional cards on teaching in the fifth grade students of Elementary School. The method used is descriptive qualitative. The researcher used observation, interview, and documentation to collect the data. The results showed that there was an increase on the students enthusiasm for learning process, and there were 27 students (69.23%) that have a score above the Minimum Criteria of Mastery (Kriteria Ketuntasan Minimal/KKM). The study concludes that the use of fractional cards able to help the learning process on the fractions material of the fifth grade students of Elementary School.